1994
DOI: 10.1105/tpc.6.10.1357
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium meliloti lipooligosaccharide nodulation factors: different structural requirements for bacterial entry into target root hair cells and induction of plant symbiotic developmental responses.

Abstract: Rhizobium meliloti produces lipochitooligosaccharide nodulation NodRm factors that are required for nodulation of legume hosts. NodRm factors are O-acetylated and N-acylated by specific Cl6-unsaturated fatty acids. nodL mutants produce non-O-acetylated factors, and nodFE mutants produce factors with modified acyl substituents. Both mutants exhlbited a significantly reduced capacity to elicit infection thread (IT) formation ln alfalfa. However, once initiated, ITs developed and allowed the formation of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
0
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(178 citation statements)
references
References 50 publications
10
163
0
5
Order By: Relevance
“…The rhizobium cell walls are composed of varying polysaccharide which provides another opportunity for plant partners choice using the ''lock and key'' cascade that determines the degree of plant and bacterial specificity [75]. Some researchers have reported that rhizobia of different genera can infect the same plant species but some plant species can strictly be infected by rhizobia from only one specific genera [78] [79].…”
Section: Host Specificity and Symbiotic Effectivenessmentioning
confidence: 99%
“…The rhizobium cell walls are composed of varying polysaccharide which provides another opportunity for plant partners choice using the ''lock and key'' cascade that determines the degree of plant and bacterial specificity [75]. Some researchers have reported that rhizobia of different genera can infect the same plant species but some plant species can strictly be infected by rhizobia from only one specific genera [78] [79].…”
Section: Host Specificity and Symbiotic Effectivenessmentioning
confidence: 99%
“…It has been demonstrated that Nod factors produced by rhizobial nod genes provoke initial plant responses leading to the formation of nodule primordia (Heidstra and Bisseling 1996). Formation of infection threads is known to be involved in the Nod factor-mediated signalling pathway (Ardourel et al 1994). In addition, bifurcated vascular bundles with abundant expression of ENOD40 are found to be induced by Nod factors alone (Stokkermans 1994;Minami et al 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Nod factor signaling leading to root hair deformation, epidermal marker gene activation, and cortical cell divisions (CCD) in Medicago spp. depends on the presence of a sulfate group at the reducing glucosamine residue on the NodSm factor, whereas additional modifications at the nonreducing end of the backbone (O-acetylation and the nature of the acyl chain) are essential only for the infectionrelated events, including formation of shepherd's crooks, infection threads and repolarization of the cytoskeleton of root hairs [37]. This strict dependency on Nod factor structure is also seen for the formation of infection threads and nodule development from cortical cell division foci in pea (Pisum sativum) [38].…”
Section: The Quest For Nod Factor Receptorsmentioning
confidence: 99%
“…It was therefore hypothesized that, in Medicago spp. and pea, two complementary perception systems operate, one triggering a signaling cascade which leads to the formation of CCDs (Bsignaling^), and the second controlling the intracellular accommodation of rhizobia (Bentry^) [37].…”
Section: The Quest For Nod Factor Receptorsmentioning
confidence: 99%
See 1 more Smart Citation